Incidence and predictors of loss to follow-up among adult HIV patients attending antiretroviral therapy at public health facilities in Agaro town, Southwest Ethiopia, 2023 - Abduljebar Mohammed Ahmed; Assefa Legesse Sisay; Mamo Nigatu Gebre (BMC Infectious Diseases)
Abstract Background Loss to follow-up from antiretroviral therapy reduces treatment benefits and leads to treatment failure and onward transmission of HIV. Appropriate interventions to increase adherence to the antiretroviral therapy (ART) cannot be designed and implemented without concrete evidence on the rate of loss to follow-up and the characteristics of those who disengage from the treatment. Hence, this study aimed to estimate the incidence of loss to follow-up and identify its predictors among HIV patients following ART at selected public health facilities in Southwest Ethiopia. Methods An Institutional-based retrospective cohort study was conducted among 357 randomly selected adult HIV patients attending antiretroviral therapy from January 2017 to December 2021 at Agaro General Hospital and Agaro Health Center. Data were entered into Epi-data version 3.1 and analyzed using STATA 14.2. To estimate and compare the survival probabilities, the Kaplan-Meier method and log-rank test were used. Cox regression analysis was fitted to identify independent predictors of time to loss to follow-up. The proportional hazard assumption was checked using the Schoenfeld residual test. The 95% CI of the hazard ratio with a corresponding p-value ≤ 0.05 was used to declare statistical significance. Results Among a cohort of 357 HIV patients followed for 1028 person-years at Agaro General Hospital and Agaro Health Center, 48 (13.4%) lost their ART follow-up. The overall incidence rate of loss to follow-up was 4.7 (95% CI 3.7, 7.3) per 100 adult-years. In multivariable Cox regression analysis, rural residence (adjusted hazard ratio (AHR) = 2.45; 95% CI:1.08–5.58), World Health Organization Clinical stage-IV (AHR = 2.65: 95% CI 1.13–6.26), not disclosing HIV serostatus (AHR = 2.51; 95% CI 1.19–5.29), availability of no treatment supporter (AHR = 4.90; 95% CI: 2.20-10.87), poor and fair adherence to ART follow-up (AHR = 11.28; 95% CI: 4.03–31.56) and (AHR = 5.98; 95% CI: 2.24–15.92), and being out of the catchment area (AHR = 2.70; 95% CI:1.21–6.06) were independently associated with loss to follow-up. Conclusion In this study, the incidence rate of loss to follow-up among adult HIV patients on ART was higher than the national average. Key predictors of loss to follow-up included rural residence, WHO Clinical stage IV, not disclosing HIV serostatus, absence of a treatment supporter, fair/poor adherence to ART, and visiting an ART clinic outside the catchment area. Therefore, to minimize loss to follow-up, targeted interventions addressing these predictors should be implemented to improve ART follow-up and care for adult HIV patients.